O papel da governança da internet dentro da governança global: um estudo de caso da ICANN - Datysgeld, Mark William (2017)
The term global governance has taken a new form in Internet Governance, where most institutions use the multistakeholder model, forming spaces for dialogue and decision-making processes with various actors, including states, companies, civil society or academia. An analysis of the ICANN case study, the institution responsible for administering contracts related to the regulation of the use of Names and Numbers, the DNS, is then proposed. The research was done through academic reading, journalism, field research, participation in conferences and interviews with people relevant to the area. With the material from these various sources, it was elaborated a panorama of the technological revolution contextualization that led to the Internet as it is today, as well as to global governance. Subsequently, we moved on to the Internet Governance ecosystem as a concept and practice. Thus, the case study is embedded in a larger context, so that one can understand it in its intricate details. Unlike most transnational institutions, which are deliberation bodies, ICANN decisions are actually carried out. Although the multistakeholder model proposes equality among the actors, some have greater influence. Prior to the IANA Transition, the United States had a much greater weight, now largely occupied by the private sector. Internet Governance is unique within global governance. It owes its distinction to some possible reasons, such as the technical drawing of the Internet. Therefore, there is a great possibility that this is not a reproducible model in other areas. The multistakeholder model presents a divergent way of assessing the relations between actors in the International System and the limit of state power. Even if there is no continuity in the current model, the field of study is extensive and still far from reaching maturity